The effect of public and private health expenditures on life expectancy in different countries: Using panel data model - Tayyebe Azodi; Mohammad Javad Razmi; Ali Akbar Naji Meidani; Mohammad Ali Falahi (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study aims to examine the factors that form the commitment Design/methodology/approach: The sampling technique used is proportionate stratified random sampling, with 100 respondents and the data collection happens in 2018. Methods of data analysis in this study uses multiple linear regression, with the number of respondents as many as 100 employees. Findings: The result shows that the competence and organizational culture significantly influence the commitment. This implies to the manager that the increase of employee competence and the suitable organization culture are very important in strengthening their employee commitment. Research limitations/implications: The limitation of this research is in the amount of variables that are only three, and only focus in one object. Originality/value: The findings of this research are the new ones, by developing the previous theory, using a new place and time.
Keywords: D80; D81; G31; G32; 330; competence; organizational culture and commitment